BOUNDARY BETWEEN THE TIMANIAN AND URALIAN TECTONIC CYCLES: RESULTS OF DATING OF DETRITAL ZIRCONS FROM BASAL HORIZONS OF THE LOWER PALEOZOIC SYNRIFT COMPLEX OF THE POLAR URALS, AND IGNEOUS ROCK AGE DATA REPORT - A. A. Soboleva; N. Yu. Nikulova; V. B. Khubanov (Геодинамика и тектонофизика)
The Upper Cambrian-Lower Ordovician terrigenous strata, unconformably overlying the Upper Riphean-Vendian rocks of the Timanide orogen in the north of the Urals, and contemporaneous bimodal volcanics and intrusive rocks are considered complexes marking the beginning of rifting which led to the opening of the Paleo-Ural Ocean later on. The article presents the results of U-Pb (LA-ICP-MS) dating of detrital zircons from sandstones lying at the base of the section of the rift complex in the Malaya Usa River basin in the Polar Urals. It was found that the clastic sequence (identified as the Khoydyshor formation) began to accumulate no earlier than the Cambrian–Ordovician transition. Zircon ages fall within the continuous Vendian to Early Ordovician (575–478 Ma) interval with peak at 512 Ma. This age range overlaps with the age of rhyolites interlayered conformably with sandstones and rhyolite porphyry dikes intruding the Khoydyshor formation, thus indicating a possible admixture of products of synsedimentary volcanism. A narrow zircon age pattern allows us to conclude that the main sources of detrital zircons in sandstones were the Early-Middle Cambrian igneous rocks formed at the stage of pre-rift uplift, and, to a lesser extent, the Late Cambrian-Early Ordovician riftogenic magmatic complexes, marking the beginning of the Uralian tectonic cycle, as well as the Late Vendian igneous rocks of the underlying Timanide orogen. Judging by the Th/U ratio, most of the detrital zircons within the sandstones were derived from the Early Paleozoic silicic volcanic and hypabyssal rocks and the Vendian granitoids and diorites. The almost complete absence of older grains, which are typical of coeval sandstones of the northern part of the Urals, may indicate the accumulation of the considered sandstones in a local trough with local clastic material sources. Probability density estimation of U-Pb ages for zircon from igneous and metamorphic rocks of the Polar Urals indicates that there were no gaps in the Late Riphean to Early Ordovician endogenous activity in this region. The main peaks occur at 552, 521 and 500 Ma, and an additional peak – at 665 Ma. The results of dating of detrital zircons from sandstones of the Khoydyshor formation together with the database of U-Pb isotope ages of igneous and metamorphic rocks of the Polar Urals (119 items), compiled by the authors, indicate that the change in geodynamic regime from collisional orogenesis in the Late Vendian to the Early-Middle Cambrian pre-rift uplift and following Late Cambrian rifting was not accompanied by a longterm discontinuity in magmatic activity.